Spectrophotometric Estimation of Flutamide in Pharmaceutical Dosage Forms - Reddy, M.N.; Murthy, T.K.; Dharma Reddy, M.; Sankar, D.G. (Asian Journal of Chemistry, 2010)
Two simple and sensitive spectrophotometric methods (methods A and B) for the estimation of flutarnide for both bulk and pharmaceutical dosage forms were developed. Method A is based on the formation of reddish pink colored chromogen with chromotropic acid having λmax at 525 nm and method B is based on the formation of yellowish brown coloured complex with resorcinol exhibiting λmax at 485 nm.